ANALYSIS OF HEAT AND MASS TRANSFER ON COOLING TOWER FILL - Abdul Aziz Rohman Hakim; Engkos Achmad Kosasih (Jurnal Forum Nuklir, 2020)
This paper discusses heat and mass transfer in cooling tower fill. In this research, dry bulb temperature at the bottom fill, ambient relative humidity, air stream velocity entering fill, dry bulb temperature leaving the fill, relative humidity of air leaving the fill, inlet and outlet water temperature of cooling tower were measured. Those data used in heat and mass transfer calculation in cooling tower fill. Then, do the heat and mass transfer calculation based on proposed approch. The results are compared with design data. The design and analogy method showed different  result. The parameter which influence the heat transfer at cooling tower are represented by coefficient of heat transfer hl and coefficient of mass transfer kl. The differencies result between design and analogy method shows that there is important parameter which different. Deeply study needed for it.